Functional adaptation rather than ecogeographical rules determine body-size metrics along a thermal cline with elevation in the Chinese pygmy dormouse (Typhlomys cinereus) - Cui, J; Lei, B; Newman, C; Ji, S; Su, H; Buesching, C; Macdonald, D; Zhou, Y (Elsevier, 2020)
Phenotypic plasticity is crucial for how organisms respond to variation in their environment, affecting their diversity and distribution, especially in the light of rapid environmental change. Ecogeographical rules predict an association between specific adaptive morphological and physiological traits with cooler conditions due to higher latitude, elevation, or climate change. Such ecogeographical effects are often most evident in ancient species due to continuous selective adaptation occurring over long periods of time. Here, we use the suitably ancient Chinese pygmy dormouse (Typhlomys cinereus) to test whether body-size, appendage length and heart size vary in accordance with Bergmann's, Allen's and Hesse's rule, respectively. Based on a sample of 67 adult individuals (female, n = 29; male n = 38) trapped at 37 sites transcending an elevational range from 414 to 1757 m, we tested for trait concordance with Bergmann's rule (body mass, length and SMI), Allen's rule (length of tail, foot, ear, snout), and Hesse's rule (wet and dry heart mass). Effects of elevation (and thus temperature lapse rate; calculated as 0.61 °C per 100 m) on body size, appendage length and heart size, were tested by fitting Standardized Major Axis (SMA) models. We observed substantial heterogeneity in morphometric traits allowing for the detection of ecogeographical clines. However, none conformed with Bergmann's, Allen's (except ear size), or Hesse's rule. However, our results indicate some support for Geist's rule of net primary productivity. We conclude that pervasive functional life-history adaptations in this blind, arboreal, echolocating ancient species exceeded selection for morphological energy efficiency constraints, with the notable exception of reduced ear pinnae size at colder, elevated sites. This is an important consideration for predicting how species, and populations in general, may adapt to human induced rapid environmental change, contrary to expectations of warming driving selection for smaller body-size.